Lessons learnt from MyCyFAPP Project: Effect of cystic fibrosis factors and inherent-to-food properties on lipid digestion in foods. (July 2020) - Calvo-Lerma, Joaquim; Asensio-Grau, Andrea; Heredia, Ana; Andrés, Ana
Graphical abstract: Highlights: Food research can have a direct impact on clinical treatments. Static in vitro digestion models allow for generating new knowledge regarding lipolysis in real foods. An evidence-based method to adjust pancreatic enzyme supplements in cystic fibrosis was developed. Food intake and host-related factors are determinants of lipolysis. Abstract: Unveiling mechanisms underpinning nutrient digestion has raised interest in the field of medical sciences for their potential application in clinical treatments. In the case of Cystic Fibrosis (CF), there exists an urgent need for understanding food lipid digestion to establish a criterion to adjust the dose of pancreatic enzyme supplements; patients have to take the supplements to allow digestion, given the associated exocrine pancreatic insufficiency (EPI). The aim of MyCyFAPP Project was to establish an evidence-based method to adjust pancreatic enzyme replacement therapy. To solve this challenge, the still unexplored field of real foods digestion had to be addressed. This review paper provides a description of the static in vitro digestion model that simulated different EPI intestinal conditions to conduct an extensive experimental work with 52 foods. Then, a summary of the data modelling that allowed for establishing a dosing criterion for enzyme supplements is provided. Following, by means of examples, an overview of the main findings related to the new knowledge generated in the field of lipid digestion in real foods is discussed, including the role of the inherent-to-food and the host factors affecting lipolysis. Finally, a discussion about the translation of the generated results in the lab to the clinical treatment of CF concludes with the lessons learnt from conducting this study.